Dynamic Navigation of Query Results Using Biased Topic Sensitive Page Rank Algorithm - Lakshmi, L; Reddy, P Bhakara (International Journal of Computer Sciences and Engineering, 2015)
The major disadvantage of Page Rank is that it favors the older pages, because a new page, even a very good one will not have many links unless it is a part of an existing site. Page Rank is a global measure and is query independent. The Rank sinks problem occurs when in a network pages get in infinite link cycles. To improve the search results Topic-Sensitive Page Rank also referred to as TSPR is a context-sensitive ranking algorithm for web search developed by Taher Haveliwala. The disadvantage with topic sensitive page rank algorithm is it uses basis set is small that is it uses 16 top level categories. So we propose to improve topic sensitive page rank algorithm with best set of basis topics. Here we propose to use fine grained set of topics mainly categorized into four categories and sub categories and so on. Almost all paths end at maximum sixth level. This method results efficient results compared page rank and context sensitive topic sensitive page rank algorithms.